Manual lymphatic drainage with comprehensive anti-diabetic therapy (MLD / CDT) as a method of treatment of lymphoedema - literature review - Płoszaj, Ola; Malińska, Małgorzata; Hagner-Derengowska, Magdalena; Kałużny, Krystian (Journal of Education, Health and Sport, 2017)
Lymphedema is an accumulation of lymph, i.e stagnation of water and proteins in extracellular space and lymphatic vessel due to impairment of its transportation as an effect of congenital disorders or lymph vessel lesion. The priority in therapeutic approach to lymphedema should be establishing the cause of edema, setting medical diagnosis and treatment method as early as possible. Complex Decongestive Therapy is recommended by International Society of Lymphology and considered as a standard in lympedema treatment irrespective of their stage of development and the cause.